Cerebral blood flow in adolescents with drug-naive, first-episode major depressive disorder: An arterial spin labeling study based on voxel-level whole-brain analysis - Xiong, Ying; Chen, Rong-Sheng; Wang, Xing-Yu; Li, Xiao; Dai, Lin-Qi; Yu, Ren-Qiang (Frontiers in Neuroscience, 2022)
Purpose: The major depressive disorder (MDD) can be a threat to the health of people all over the world. Although governments have developed and implemented evidence-based interventions and prevention programs to prevent MDD and maintain mental health in adolescents, the number of adolescents with this condition has been on the rise for the past ten years. Methods: A total of 60 adolescents were recruited, including 32 drug-naive adolescents with first-episode MDD and 28 healthy controls (HCs). Alterations in the intrinsic cerebral activity of the adolescents with MDD were explored using arterial spin labeling (ASL) while differences in the regional cerebral blood flow (rCBF) of the two groups were assessed based on the voxel-based whole-brain analysis. Finally, correlations between the regional functional abnormalities and clinical variables were investigated for adolescents with MDD. Results: MDD patients had lower rCBF in the left triangular part of inferior frontal gyrus (IFGtriang) but higher rCBF in the right Percental gyrus (PreCG) compared with HCs. Negative correlations were also noted between the CBF in the left IFGtriang and the HAMD scores of MDD patients. Conclusion: Elucidating the neurobiological features of adolescents’ patients with MDD is important to adequately develop methods that can assist in early diagnosis, precaution and intervention.